Intralesional copper wire retention and pingyangmycin injection: an effective combinational therapy for complex venous malformation in soft tissue. (April 2014) - Yuan, S-M; Hong, Z-J; Jiang, H-Q; Wang, J; Hu, X-B
Objectives: Complex venous malformations (VMs) may extensively involve the soft tissue. The treatment remains a challenge till now. Here we introduce a combinational therapy of copper wires and pingyangmycin (bleomycin A5, PYM). Methods: Copper wires were retained in VMs by repeated penetration with a straight needle. Subsequently, PYM solution was injected into the lesion. Eight to 10 days later, copper wires were removed. The dressing was changed every day until the puncture pores healed. Magnetic resonance imaging scanning was performed to observe the change of VMs. Results: From January 2001 to December 2011, 56 patients were treated. During the follow-up period, most of the VMs shrunk obviously. The symptoms were relieved or disappeared. The complications included local pain, temporary paraesthesia and moderate fever, which disappeared quickly after the removal of copper wires. Conclusions: This combinational therapy is a safe and effective approach for the complex VMs in soft tissue.